2010
DOI: 10.3177/jnsv.56.34
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina Prevents Atherosclerosis by Reducing Hypercholesterolemia in Rabbits Fed a High-Cholesterol Diet

Abstract: SummaryThe anti-atherogenic effects of spirulina ( Spirulina platensis ) were investigated in the New Zealand White (NZW) rabbit model. The animal had hypercholesterolemia induced by being fed a high cholesterol diet (HCD) containing 0.5% cholesterol for 4 wk, and then fed a HCD supplemented with 1 or 5% spirulina (SP1 or SP5) for an additional 8 wk. Spirulina supplementation lowered intimal surface of the aorta by 32.2 to 48.3%, compared to HCD. Serum triglyceride (TG) and total cholesterol (TC) significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 33 publications
5
47
0
3
Order By: Relevance
“…This is in consistent with previous findings in rats (Kato et al, 1984) hamsters (Riss et al, 2007) rabbits (Cheong et al, 2010) and human (Ruitang & Chow, 2010). Although the mechanism by which the SPP reduces CHO has not been fully examined, the hypocholesterolemic actions of SPP involve reducing plasma and liver CHO levels due to the increase in lipoprotein lipase and hepatic triglyceride lipase activity (Karkos et al, 2008), inhibition of both jejunal CHO absorption and ileal bile acid resorption (Nagaoka et al, 2005), in addition to modifying lipoproteins metabolism (decrease of low density lipoprotein and increase of high density lipoprotein; Torres-duran et al, 2007).…”
Section: Biochemical Parameterssupporting
confidence: 94%
“…This is in consistent with previous findings in rats (Kato et al, 1984) hamsters (Riss et al, 2007) rabbits (Cheong et al, 2010) and human (Ruitang & Chow, 2010). Although the mechanism by which the SPP reduces CHO has not been fully examined, the hypocholesterolemic actions of SPP involve reducing plasma and liver CHO levels due to the increase in lipoprotein lipase and hepatic triglyceride lipase activity (Karkos et al, 2008), inhibition of both jejunal CHO absorption and ileal bile acid resorption (Nagaoka et al, 2005), in addition to modifying lipoproteins metabolism (decrease of low density lipoprotein and increase of high density lipoprotein; Torres-duran et al, 2007).…”
Section: Biochemical Parameterssupporting
confidence: 94%
“…This property has been observed under pathogenic conditions, however, such as in rabbits fed high cholesterol diets in which 0.5 g/d of spirulina increased serum levels of high density lipoproteins (HDL), the latter representing a protective factor against atherosclerosis (Colla et al, 2008). In a similar trial, supplementations of 1% and 5% spirulina were shown to be effective in reducing serum total cholesterol and low density lipoproteins (LDL) levels in hypercholesterolemic rabbits (Cheong et al, 2010). On the other hand, contrary to that observed in serum parameters, spirulina did not appear to lower carcass fatness in rabbits fed high fat diets when compared to those fed low-fat diets (Meineri et al, 2009).…”
Section: Resultsmentioning
confidence: 82%
“…15 Spirulina is not a new drug as its story as a nutritional element is quite old, dating back to the Aztecs. 28 Inhibitory effects of Spirulina on atherosclerosis were reported 29 possibly via the inhibition of leptin secretion and improvement of leptin resistance. Previous studies support the beneficial effects of Spirulina against fatty liver, 30,31 oxidative stress, 32 hyperglicemia, 33,34 hypercholesterolemia, 35 and arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%